2013
DOI: 10.1177/0194599812472319
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐Specific Self‐Efficacy in Spasmodic Dysphonia Patients

Abstract: SD patients established on botulinum toxin injections have high degrees of general and disease-specific SE. Patients with higher SE-SD demonstrate lower vocal handicap and lower levels of anxiety and depression. A 13-item disease-specific SE-SD scale has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
8
0
3
Order By: Relevance
“…Previous studies have shown that SE is a strong predictor of health behaviors. 21 , 22 , 23 , 24 , 25 , 26 SE affects rates of smoking cessation 21 and adherence to therapy for chronic diseases, like diabetes. 22 SE has also been studied in various voice disorders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that SE is a strong predictor of health behaviors. 21 , 22 , 23 , 24 , 25 , 26 SE affects rates of smoking cessation 21 and adherence to therapy for chronic diseases, like diabetes. 22 SE has also been studied in various voice disorders.…”
Section: Methodsmentioning
confidence: 99%
“… 22 SE has also been studied in various voice disorders. 23 , 24 , 25 , 26 The GSES is a 10 question scale where patients rate statements from 1 to 4. Total scores range from 10 to 40 and higher scores indicate higher degrees of SE.…”
Section: Methodsmentioning
confidence: 99%
“…Die laryngeale Dystonie ist eine fokale Dystonie und stellt neben der Kommunikationsstörung durch Stimm- und/ oder Atembeschwerden für die Betroffenen eine erhebliche körperliche Beschwerde dar. Im Falle einer Stimmstörung ist der Grad der Behinderung (GdB) mit 20-30 einzuschätzen und kann im Falle einer Dyspnoe auch darüber liegen [4][5][6][7]. Frauen sind im Vergleich zu Männern zweimal häufiger betroffen.…”
Section: Introductionunclassified
“…O uso de TB é considerado o tratamento mais utilizado para a DLAD (Ludlow et al, 1988;Aronson et al, 1993;Adams et al, 1995;Woodson, 1995;Wong et al, 1995a;Inagi et al, 1996;Lindestad et al, 1997;Zwirner et al, 1997;Finnegan et al, 1999;Ludlow, 2000;Galardi et al, 2001;Langeveld et al, 2001;Boutsen et al, 2002;Tish et al, 2003;Adler et al, 2004;Cannito et al, 2004;Blitzer, 2005;Wingate et al, 2005;Baylor et al, 2007;Cannito et al, 2008;Ludlow et al, 2008;Paniello et al, 2009;Blitzer, 2010;Elmiyeh et al, 2010;Novakovic et al, 2011;Fulmer et al, 2011;Cannito et al, 2012ab;Dejonckere et al, 2012;Gama et al, 2012;Damrose, 2012;Hu et al, 2013;Rosow et al, 2013), sendo aplicado, principalmente, no músculo TA, apresentando alívio dos síntomas no segundo ou terceiro dia. Após a ação do medicamento, o tratamento atinge a estabilidade após duas semanas, quando se percebe melhora na qualidade da voz (Ludlow et al, 1988;Boutsen et al, 2002;Blitzer, 2010;Cannito et al, 2012a).…”
Section: Discussionunclassified
“…Após mais de duas décadas de estudos, ainda não há consenso quanto A identificação dos sinais e sintomas, bem como a eficiência no tratamento com TB para indivíduos com DLAD, tem sido bastante documentada por meio de estudos que apresentam análise perceptivo-auditiva (Ludlow et al,1988;Truong et al 1991;Adams et al,1995;Boutsen et al, 2002;Tish et al, 2003;Cannito et al, 2004;Blitzer, 2005;Eadie et al, 2007;Cannito et al, 2008;Braden et al, 2010;Cannito et al, 2012ab;Silverman et al, 2012;Hu et al, 2013); análise espectrográfica (Ludlow et al, 1988;Boutsen et al, 2002;Cannito et al, 2004;Rees et al, 2007;Cannito et al, 2008;Gama et al, 2012); análise acústica de parâmetros vocais (Adams et al, 1995;Zwirner et al, 1997;Sapienza et al, 1998;Boutsen et al, 2002;Kendall et al, 2011;Cannito et al, 2012ab); parâmetros aerodinâmicos (Finnegan et al, 1999;Boutsen et al, 2002) e impacto vocal na qualidade de vida e autopercepção (Aronson et al, 1993 ;Adams et al, 1995;Liu et al, 1996;Lindestad et al, 1997;Wingate et al, 2005 ;Paniello et al, 2009;Braden et al, 2010;Elmieyeh et al, 2010;Novakovic et al, 2011;Dejonckere et al, 2012;…”
Section: Discussionunclassified